Sistem e-Commerce Penjualan Handphone Baru dan Second Pada Sinar Cell Selong Lombok Timur - Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; Ahmad Farijan; Muhammad Irwan Suryadi (STMIK Budi Darma, 2021)
E-commerce is a process of trade transactions between sellers and buyers by utilizing internet media online to save operational costs such as paper, ink, and catalog printing. Sinar Cell is a cellular shop that is engaged in selling cellular devices in the form of new and used cellphones that have many customers spread across the West Nusa Tenggara region. Currently, the sales procedure at Sinar Cell stores is still conventional, where customers come directly to the store or make transactions by telephone because they do not have online marketing media. Based on this, a sales e-commerce application is needed which is developed using the SDLC (System Development Lifecycle) method using PHP programming and My SQL database. This application can help companies promote their products and make it easier to manage sales. In addition, it can help customers to get product-related information quickly and can place orders directly without space and time limits.